Specific Changes of Chromatin Structure in Nuclei of Normal Epithelium Adjacent to Laryngeal Squamous Cell Carcinoma - Thomas Dreyer; Iris Knoblauch; David Garner; Alexei Doudkine; Calum MacAulay; Branko Palcic; Christian Popella (Analytical Cellular Pathology)
The aim of this study was to confirm the existence of specific nuclear texture feature alterations of histologically normal epithelial borders nearby invasive laryngeal cancer (NC).